REPRESENTASI PEREMPUAN DALAM SYAIR ARDAN: KAJIAN FEMINISME - Maiyang Resmanti; Asep Yudha Wirajaya (Kantor Bahasa Provinsi Maluku, 2022)
This paper is the result of a study that reviews Syair Ardan which is studied with feminism theory. Syair Ardan tells the phenomenon of women living in patriarchal culture and their opposition both directly and indirectly. The types of research used are descriptive qualitative research, data collection techniques with library, read, and take note techniques. The data are validated by theoretical triangulation. Data analysis techniques are in the form of data classification, data reduction, and data analysis. This paper contains the explanation of the representation of women who are able to develop their abilities and take part in the public sphere. Zuhrah was the daughter of the King who could become a woman who was good at self defence and using weapons. She was also able to become a wise king, set the right policies or regulations, and be respected by the ministers and their people in the midst patriarchal culture. However, Zuhrah was not shown as a female king, but a female king disguised as a male. It seems that the co-author chose to side with the acceptance of the text which still adhered to the patriarchal culture.Tulisan ini merupakan hasil kajian yang mengulas Syair Ardan yang dikaji dengan teori feminisme. Syair Ardan mengisahkan fenomena perempuan yang hidup di kebudayaan patriarkat dan upayanya menyamaratakan peran gender baik secara langsung maupun tidak langsung. Jenis penelitian yang digunakan adalah penelitian deskriptif kualitatif, teknik pengumpulan data dengan teknik pustaka, simak, dan catat. Data diabsahkan dengan triangulasi teoretis. Teknik analisis data berupa klasifikasi data, reduksi data, dan analisis data. Tulisan ini berisi penjelasan mengenai representasi perempuan yang mampu mengembangkan kemampuan dirinya dan berperan di wilayah publik. Zuhrah adalah putri Raja yang mampu menjadi perempuan pandai bela diri, pandai menggunakan senjata, menjadi raja yang bijaksana, dapat menetapkan kebijakan atau regulasi yang tepat, dan disegani menteri serta rakyatnya di tengah kebudayaan patriarkat. Namun, Zuhrah tidak ditampakkan sebagai raja perempuan, tetapi raja perempuan yang menyamar sebagai laki-laki. Agaknya penyalin memilih berpihak pada keberterimaan teks yang masih berpegang teguh pada kebudayaan patriarkat.